Dylematy i problemy związane z wykorzystywaniem w warunkach polskich modeli oceny zagrożenia upadłością - Rogowski, Waldemar (Methodological Dilemmas and Problems Application of Bunkruptcy Models in Poland, 2007)
This paper focuses on methodological dilemmas and problems related to creating and practical application of bankruptcy models. Pros and cons of quantitative approach to bankruptcy prediction are major areas of this study. This paper is an attempt to answer the question what kind of relation exists between classical financial analysis and bankruptcy model. The general requirements for these models are also formulated there
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1159, s. 320-327